KEDUDUKAN HUKUM AGEN ASURANSI BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Cornelia Alpha; Ariawan Gunadi (Jurnal Hukum Adigama, 2022)
Insurance agents play an important role in the success of insurance companies. They are in charge ofrepresenting their company in marketing the products that they sell, as well as providing assistance infiling company documents and performing transactions with the customers of their company. The basisof cooperation between insurance agents and their company is an agency agreement that containselements that revolves around work, orders and wages agreed upon by both the insurance companyand their agents who are assigned to represent the company whenever they interact and provideservices to their customers. This is a normative research with descriptive methods. The resultsconcluded from this research is that the position of the insurance agents can not be regulated directlyin the Manpower Act. Insurance agents are only freelance workers who have signed an agreement thatis subject to the provisions of Article 1320 and Article 1338 of the Civil Code. The agency agreementitself fulfills the characteristics of a work agreement that contains elements that revolves around work,orders and wages. However, insurance agents themselves can be classified as workers who work andreceive wages.